Effect of Natural or Artificial Feed on Growth of Tilapia (Oreochromis niloticus) - Stenly M.B.S Wairara; Rosa D. Pangaribuan (Faculty of Agriculture Musamus University, 2020)
The purpose of this study was to analyze the composition of nutrients contained in kopyok moss and analyze the effect of natural or artificial feed on the growth of tilapia (Oreochromis niloticus). This research was carried out in October-November 2019, met in the UNPUS MSP laboratory and used the experimental method and Completely Randomized Design (CRD). Test animals used were juvenile tilapia 5-7 g; 5-10 cm and totaling 27 individuals. The fish were divided into three treatment groups, namely P1 (PF500 MS PRIMA FEED feed group), P2 (Takari feed group), and P3 (kopyok moss natural feed group) and each group consisted of nine fish. Feeding is done twice a day on an ad libitum basis for 30 days continuously. The results showed that the absolute weight gain in the P2 group was higher than in the P1 and P3 groups, the absolute length increase in P3 was higher than in P1 and P2 and the survival rate of P2 was higher than in P1 and P3. This explains that the nutritional content, especially protein in the feed, must be in the amount needed, otherwise the excess protein will be released into the environment in the form of ammonia (NH3), increased ammonia toxicity can cause damage to the gills and kidneys, decreased growth, disruption of the brain system, and dissolved oxygen levels become low. Based on the results of the study it can be concluded that protein is one of the essential nutrients for growth for survival, but it must be at the amount needed by the body so that it is not released to the environment which will reduce water quality.